2005
DOI: 10.1016/j.cattod.2005.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-controlled reactivity of carbonaceous materials towards oxidation

Abstract: Carbon samples are being investigated with thermogravimetry, infrared spectroscopy and transmission electron microscopy. We focus on a spark discharge soot, soot from a heavy-duty diesel engine, soot from a diesel engine in black smoking conditions and a furnace carbon black from Degussa. The aim of this study is to correlate reactivity towards oxygen, functional groups and nanostructure. It is found that the amount of defects as well as the functionalisation plays an important role in the onset of combustion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(99 citation statements)
references
References 18 publications
(14 reference statements)
8
89
0
1
Order By: Relevance
“…Application of various technical solutions in modern compression ignition engines relating to composition of diesel oils, power systems as well as modification with the use of various technical agents of the process of combustion of the mixture of fuel and oil would lead to formation of different structures of soot particles (Fig. 1) [5][6][7]. The types of these structures have a significant influence upon designing of supports and catalytic layers of FCS (Fluorescence Correlation Spectroscopy) and it may affect physical and chemical parameters of soot layers deposited on the wall of a support cell and the process of filter regeneration [8].…”
Section: The Mechanism Of Formation Of Pmmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of various technical solutions in modern compression ignition engines relating to composition of diesel oils, power systems as well as modification with the use of various technical agents of the process of combustion of the mixture of fuel and oil would lead to formation of different structures of soot particles (Fig. 1) [5][6][7]. The types of these structures have a significant influence upon designing of supports and catalytic layers of FCS (Fluorescence Correlation Spectroscopy) and it may affect physical and chemical parameters of soot layers deposited on the wall of a support cell and the process of filter regeneration [8].…”
Section: The Mechanism Of Formation Of Pmmentioning
confidence: 99%
“…2) and standards of emission of toxic components of exhaust gases complied by the engine [6,11,12]. The division of soot according to the last criterion is mainly ascribed to the change of generation of power systems with direct injection of fuel (change of such parameters as injection pressure, droplet size and dose division), optimization of combustion process as well as aftertreatment system (Tab.…”
Section: Influence Of Exhaust Gas Aftertreatment Systems Upon Formatimentioning
confidence: 99%
“…In fact, the high number density at which diesel or biodiesel particles are still emitted in urban areas are thought to exacerbate respiratory, cardiovascular, and allergic diseases due to their small respirable size, large surface area, surface reactivity, hygroscopicity, and potential toxicity (Bernstein et al, 2004;Turrio-Baldassarri et al, 2004;Müller et al, 2005;Reff et al, 2007;Popovicheva et al, 2008;Russell et al, 2009;Topinka et al, 2012;Steiner et al, 2013;Popovicheva et al, 2014a). Specifically, the toxicological properties of diesel and biodiesel PM have been studied by Libalova et al (2016) and showed that human lung cells exposed 24 h to such emission expressed deregulated genes, especially those involved in antioxidant defense and cell cycle regulation and proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between particulate properties and reactivity has been the subject of several previous studies. Müller et al (2005Müller et al ( , 2006 investigated the oxidative reactivity of par-ticulate matter from different sources and found that the internal nanostructure controlled the particle oxidative reactivity. Vander Wal and Tomasek (2003) found that the oxidation rate could differ by more than 400% depending on the initial particle nanostructure.…”
Section: Introductionmentioning
confidence: 99%